Understanding the effect of exposure of human pathogens to polluted surface water: Salmonella as a model organism - Munir, Maliha Nuzhat (BRAC Univeristy, 2018)
This thesis report is submitted in partial fulfilment of the requirement for the degree of B.Sc in Microbiology, 2018.